DOI: 10.31274/etd-180810-1918
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the control of Listeria monocytogenes on uncured, no-nitrate-or-nitrite-added meat products

Abstract: Introduction Materials and Methods Results and Discussion Conclusions References v CHAPTER 5. GENERAL CONCLUSIONS APPENDICIES ACKNOWLEDGEMENTS massaged or pumped cured meats. Table 2.1 lists the maximum parts per million for each of the four curing agents permitted in meat and poultry products and are based on the curing method used during the production process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 85 publications
1
23
0
Order By: Relevance
“…Schrader (2010) found greater L. monocytogenes growth on 5 of 8 brands naturally cured brands of frankfurters and 3 of 5 brands of naturally cured ham than on traditionally cured controls. It should be noted that, at the time of this study, processors of naturally cured products included sodium lactate, a well recognized antimicrobial.…”
Section: Correlation Of Measured Physio-chemical Properties To L Monmentioning
confidence: 85%
See 1 more Smart Citation
“…Schrader (2010) found greater L. monocytogenes growth on 5 of 8 brands naturally cured brands of frankfurters and 3 of 5 brands of naturally cured ham than on traditionally cured controls. It should be noted that, at the time of this study, processors of naturally cured products included sodium lactate, a well recognized antimicrobial.…”
Section: Correlation Of Measured Physio-chemical Properties To L Monmentioning
confidence: 85%
“…Two replicates were conducted. More specific information on the bacterial challenge studies and the results of these studies can be found in Jackson, Sullivan, Kulchaiyawat, Sebranek, andDickson (2011) for C. perfringens andSchrader (2010) for L. monocytogenes.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
“…51,52 Naturally cured products have cured meat characteristics similar to conventionally cured meats, 18 but the naturally cured products have less pathogen controls. 19,20 While the amount of ingoing nitrite affects the extent of nitrosation/nitrosylation reaction product formation, the natural curing process does not appear to result in a significant shift of nitrite reaction products. This would suggest that it is more important to increase the amount of ingoing nitrite in naturally cured products than increase the rate of nitrite formation from nitrate.…”
Section: ■ Resultsmentioning
confidence: 99%
“…13−16 However, by utilizing natural nitrate sources, primarily celery juice/powder, and a nitrate-reducing starter culture, nitrite can be formed in natural and organic processed meats and will produce characteristics similar to conventionally cured products that are produced with direct addition of sodium nitrite. 17,18 While these naturally cured products look and taste like traditionally cured meats, Jackson et al 19 and Schrader 20 found increased risk for the growth of Clostridium perf ringens and Listeria monocytogenes, respectively. Many factors can impact pathogen growth in cured meats, but it is likely related at least in part to the curing process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Thus, RTE meat and poultry products manufactured under uncured, natural, or organic methods are sometimes termed "alternatively cured" or "naturally cured". The requirements for these products suggest that they are likely to be at a greater risk than their conventional counterparts for growth of L. monocytogenes if contamination occurs, and previous reports have supported this concern as well [5][6][7].…”
Section: Introductionmentioning
confidence: 97%